CRT in Patients with Heart Failure: Time Course of Perfusion and Wall Motion Changes - Alessia Gimelli; Paolo Frumento; Guido Valle; Mario Stanislao; Umberto Startari; Marcello Piacenti; Paolo Marzullo (Cardiology Research and Practice)
In patients treated with CRT no data relative to the relationship between regional wall motion and perfusion and reverse remodelling of the left ventricle at short and medium term followup were available. To this aim, 36 heart failure patients were studied by G-SPECT before (T0), within 2 months (T1) and 6 months (T2) after CRT. A clinical followup was completed for 36 months. In 30/36 patients there was an improvement of NYHA Class at T1 that persisted at T2. G-SPECT showed significant improvement of perfusion at T1 in 92% of patients without further changes at T2. A reduction of LV volumes, an increase of EF and an improvement of regional wall motion and thickening were observed at T1 versus baseline, with only minor changes at T2. Moreover, baseline extension of perfusion defects was scarcely correlated with improvement after CRT. Finally, end diastolic volume, perfusion defect and diabetes mellitus were independent predictors of survival. The main effects of CRT on regional myocardial perfusion and wall motion are obtained within 2 months. Volume overload modulates recovery of ventricular function independently of reperfusion and, with extension of perfusion abnormalities and diabetes were independent predictors of survival during followup.